1991
DOI: 10.1113/jphysiol.1991.sp018616
|View full text |Cite
|
Sign up to set email alerts
|

A motor programme for the initiation of forward‐oriented movements in humans.

Abstract: SUMMARY1. The EMG sequence activated before the initiation of a number of fast forwardoriented voluntary movements was analysed quantitatively in normal subjects.2. The sequence consisted of an initial inhibitory component directed to the soleus motor nucleus, followed by a second excitatory one directed to the tibialis anterior (TA).3. The spectrum of functional utilization included motor tasks in which the prime movers are leg and thigh muscles (initiation of gait, rising on tip-toes), thigh and trunk muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
261
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(278 citation statements)
references
References 26 publications
16
261
1
Order By: Relevance
“…Similarly to what was observed during the first phase of sit-to-stand and stand-tosit, stereotyped activity patterns have been demonstrated during the first phase of gait initiation (Brunt et al, 1991;Brunt et al, 1999;Crenna et al, 1991;Elble et al, 1994;Fiolkowski et al, 2002;Shapiro et al, 1981). The inhibition of the tonically active soleus followed by the activation of the tibialis anterior early in gait initiation (Crenna et al, 1991;Elble et al, 1994;Jian et al, 1993) enable the backward displacement of the centre of pressure (Brunt et al, 1991;Crenna et al, 1991), contributing to postural stability (Massion, 1992;McIlroy et al, 1999), as well as the optimum generation of momentum at the end of the first step to reach the steady-state gait (Lepers et al, 1995).…”
Section: -Postural Control Dysfunction In the Ipsilesional Sidementioning
confidence: 92%
See 1 more Smart Citation
“…Similarly to what was observed during the first phase of sit-to-stand and stand-tosit, stereotyped activity patterns have been demonstrated during the first phase of gait initiation (Brunt et al, 1991;Brunt et al, 1999;Crenna et al, 1991;Elble et al, 1994;Fiolkowski et al, 2002;Shapiro et al, 1981). The inhibition of the tonically active soleus followed by the activation of the tibialis anterior early in gait initiation (Crenna et al, 1991;Elble et al, 1994;Jian et al, 1993) enable the backward displacement of the centre of pressure (Brunt et al, 1991;Crenna et al, 1991), contributing to postural stability (Massion, 1992;McIlroy et al, 1999), as well as the optimum generation of momentum at the end of the first step to reach the steady-state gait (Lepers et al, 1995).…”
Section: -Postural Control Dysfunction In the Ipsilesional Sidementioning
confidence: 92%
“…The inhibition of the tonically active soleus followed by the activation of the tibialis anterior early in gait initiation (Crenna et al, 1991;Elble et al, 1994;Jian et al, 1993) enable the backward displacement of the centre of pressure (Brunt et al, 1991;Crenna et al, 1991), contributing to postural stability (Massion, 1992;McIlroy et al, 1999), as well as the optimum generation of momentum at the end of the first step to reach the steady-state gait (Lepers et al, 1995). Recent studies have demonstrated that subcortical post-stroke subjects present failure in modulating the soleus timing in both contralesional and ipsilesional limbs (Sousa et al, 2015a), which is associated with a decreased backward displacement of the centre of pressure (Sousa et al, 2015a(Sousa et al, , 2015b.…”
Section: -Postural Control Dysfunction In the Ipsilesional Sidementioning
confidence: 99%
“…Such a reduction in forward momentum would result in decreased forward COM in the older adults during the early stage of GI. During GI, inhibition of the tonic soleus and the activity of the tibialis anterior of both the swing and stance limbs are responsible for the backward movement of COP [26][27][28] . Swing limb hip abductors also create movement of COP toward the swing limb 29) .…”
Section: Discussionmentioning
confidence: 99%
“…Moment M a of resistance in a sound ankle joint during foot dorsiflexion is shown in Figure 3c; it correlates to the pattern of the foot flexor performance (EMG signal versus stance events) (49). The mostly concave shape of the curve indicates initiation of dorsiflexion does not encounter a large amount of resistance from the plantarflexors.…”
Section: Influence Of Moment Of Resistance In Prosthetic Ankle On Gaitmentioning
confidence: 99%